2019
DOI: 10.1002/jaba.598
|View full text |Cite
|
Sign up to set email alerts
|

Toward accurate inferences of response class membership

Abstract: In their review of synthesis within the functional analysis (FA) literature, Slaton and Hanley (2018) reported that most synthesized contingency analyses have included multiple topographies of problem behavior in the reinforcement contingency class. This leaves the question of whether one, some, or all forms of problem behavior are sensitive to the synthesized reinforcement contingencies in published analyses. To address this ambiguity, all topographies of problem behavior that were reported by caregivers to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…A summary of the information gleaned from indirect and descriptive assessments that led researchers to analyze mand compliance may be of some utility to those tasked with assessing and treating problem behavior. Across all reviewed studies, researchers reported similar caregiver reports and observations that can be characterized in the following manner: Participants emitted frequent requests for items (e.g., a computer), activities (e.g., playing a board game), social interactions (e.g., conversing about dinosaurs), environmental arrangements (e.g., having papers and crayons organized a certain way), and for adults to behave in particular ways (e.g., imitating a cartoon character's voice and dialogue; see Bowman et al, 1997, Schmidt et al, 2017, and Warner et al, 2020 for detailed examples of participant requests). Some participants reportedly recruited only a particular type of reinforcer (e.g., the participant in Torres‐Viso et al, 2018, only requested environmental rearrangement); however, it was more often reported that the reinforcers requested were heterogeneous, idiosyncratic, and complex (e.g., Daryl in Schmidt et al, 2017, requested that adults talk like animals while engaging in conversations with inanimate objects, as well as play board games following special rules that always allowed Daryl to win).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the information gleaned from indirect and descriptive assessments that led researchers to analyze mand compliance may be of some utility to those tasked with assessing and treating problem behavior. Across all reviewed studies, researchers reported similar caregiver reports and observations that can be characterized in the following manner: Participants emitted frequent requests for items (e.g., a computer), activities (e.g., playing a board game), social interactions (e.g., conversing about dinosaurs), environmental arrangements (e.g., having papers and crayons organized a certain way), and for adults to behave in particular ways (e.g., imitating a cartoon character's voice and dialogue; see Bowman et al, 1997, Schmidt et al, 2017, and Warner et al, 2020 for detailed examples of participant requests). Some participants reportedly recruited only a particular type of reinforcer (e.g., the participant in Torres‐Viso et al, 2018, only requested environmental rearrangement); however, it was more often reported that the reinforcers requested were heterogeneous, idiosyncratic, and complex (e.g., Daryl in Schmidt et al, 2017, requested that adults talk like animals while engaging in conversations with inanimate objects, as well as play board games following special rules that always allowed Daryl to win).…”
Section: Resultsmentioning
confidence: 99%
“…The abovementioned replications of Bowman et al assessed the mand compliance contingency in isolation, usually following inconclusive standard functional analysis results (e.g., Iwata et al, 1982/1994). In addition, a growing number of researchers have included the contingency in initial, interview‐informed synthesized contingency analyses (IISCAs; Hanley et al, 2014) when caregivers reported its possible relevance to severe problem behavior via open‐ended interviews (Ghaemmaghami et al, 2016; Ghaemmaghami et al, 2018; Hanley et al, 2014; Jessel et al, 2016; Jessel, Hanley et al, 2019; Jessel et al, 2018; Jessel, Metras et al, 2019; Rose & Beaulieu, 2019; Slaton et al, 2017; Warner et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…This tactic not only minimizes escalation of PB and thereby promotes safety during the analysis, but it also does not appear to confuse interpretations regarding the variables controlling dangerous PB. A study by Warner et al (2019) demonstrated that less dangerous responses reported to precede or co-occur with more dangerous forms were highly likely to be maintained by the same synthesized reinforcement contingency when all topographies were subjected to analysis. Inferences from open contingency classes and synthesized contingencies are therefore considered reasonable trade-offs for the lack of demonstration of control over each topography of PB or of the relevance of each component reinforcement contingency.…”
Section: Rationale or Underlying Theorymentioning
confidence: 99%
“…In addition, rather than arrange putative reinforcement for only dangerous behavior (Iwata et al 1982(Iwata et al /1994, IISCAs arrange reinforcement for the target dangerous behavior (e.g., SIB) as well as all other forms of PB (i.e., precursor responses, e.g., yelling and foot stomping) that are reported to co-occur with the more dangerous forms of PB (Jessel et al 2016). By opening the class of behavior topographies that may receive reinforcement in the FA, analyses are safer to conduct, and successful outcomes are more quickly achieved (Warner et al 2019). Last, only one variable differs between the rapidly alternating test and control conditions of the IISCA: the presence or absence of the synthesized reinforcement contingency.…”
mentioning
confidence: 99%
“…With regard to predicting precursors to problem behaviors, it is possible that including multiple modalities involving movements, physiology, social orientations and facial expressions could improve prediction accuracies and robustness. These modalities may directly capture the measurable indicators of emotional states of a child that may lead to problem behaviors such as fidgeting, arm crossing, cursing and grimacing [ 31 ]. Indeed, a recent study found that movement data along with annotated behaviors could build a machine learning model to predict episodes of SIB [ 32 ] but focused on prediction of problem behaviors themselves rather than precursors.…”
Section: Introductionmentioning
confidence: 99%